2020
DOI: 10.1021/acs.jpclett.0c00805
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Red-Luminophore-Forming Domain in Serum Albumin–Gold Complexes

Abstract: Serum albumin–gold complexes exhibit UV-excitable red luminescence (λem = 640 nm) with unusual Stokes shifts compared with the innate UV/blue fluorescence arising from the aromatic residues. In order to understand the mechanism of this luminescence, we employed limited proteolysis and molecular cloning techniques and assessed the domain containing the red luminophore in bovine serum albumin (BSA) and human serum albumin (HSA). We identified that the luminophore is localized in a domain of serum albumin, residi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…The same authors concluded that cysteine, 34 of which form disulfide bonds in BSA, is the binding site of Au(III) but not the location of the red-emitting fluorophore. Recently, the same research group identified the Au(III) binding domain of BSA and localized the origin of red fluorescence within the N-terminal domain using limited proteolysis and molecular cloning techniques based on luminescence measurements [ 11 ]. However, the changes and evolution in fluorescent properties are primarily connected to global changes in BSA–gold complexes dependent on the pH value and accompanied by significant structural changes on the atomic level as observed by small-angle X-ray scattering and infrared spectroscopy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors concluded that cysteine, 34 of which form disulfide bonds in BSA, is the binding site of Au(III) but not the location of the red-emitting fluorophore. Recently, the same research group identified the Au(III) binding domain of BSA and localized the origin of red fluorescence within the N-terminal domain using limited proteolysis and molecular cloning techniques based on luminescence measurements [ 11 ]. However, the changes and evolution in fluorescent properties are primarily connected to global changes in BSA–gold complexes dependent on the pH value and accompanied by significant structural changes on the atomic level as observed by small-angle X-ray scattering and infrared spectroscopy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 The domain of this Au(III) binding was recently identified. 8 Other than for bovine and human serum albumins, 8 the red luminescence has been reported for ovalbumin, 9 trypsin, 10 insulin, 11 lactotransferrin, 12 pepsin, 13 horseradish peroxidase, 14 papain, 15 and lysozyme 16 (Supporting Information, Figure S1). For example, BSA is a 66.4 kDa transport protein; ovalbumin (OVA) is a 42.7 kDa protein constituting most of egg white; trypsin is a 23.3 kDa protease; insulin is a 5.7 kDa hormone (Figure S2).…”
mentioning
confidence: 99%
“…For BSA, we analyzed within the previously identified Au(III)-binding domain. 8 We expanded the analysis to all proteins in the literature for the red luminescence, 12−16 as well as to proteins (α-2-macroglobulin and trypsin inhibitor) that did not yield the red luminescence by the Standard protocol (Figure S14).…”
mentioning
confidence: 99%
See 2 more Smart Citations